Budikdamber for Nutrition and Green Entrepreneurship in Boarding Schools in Sayum Saba, North Sumatera - Zuliyanti Siregar, Ameilia; Anggreiny; Sojuangan Siregar, Dolly; Syahril, Muhammad (UPT Publikasi Ilmiah UNISBA, 2026)
This community engagement program aims to implement Budikdamber (Budidaya Ikan dalam Ember), or fish cultivation in buckets, as a tool for applied science learning and nutrition literacy at Ma’had Tahfidz Yatim Duafa Kitabina, North Sumatra. The problems of the Sayum Sabah Islamic boarding school include limited knowledge, inadequate facilities and infrastructure, and ineffective land management. The program focuses on improving students’ knowledge, attitudes, and skills related to simple aquaponics while strengthening food security within the boarding school. A participatory approach was applied through needs assessment, theoretical training, hands-on unit assembly, field mentoring, and pre-test and post-test evaluation. Results indicated significant improvement in knowledge and skills, reflected in a more uniform level of understanding among participants post-intervention (the pre-test was 53.63 (N = 44; SD = 12.11), while the average post-test score increased to 66.36 (N = 44; SD = 10.06)). Field observations highlight strong enthusiasm, the ability to assemble functional units, and the emergence of peer teaching among students. Beyond serving as a practical science medium, Budikdamber drives community empowerment by strengthening food security, enhancing nutrition literacy, and fostering eco-friendly entrepreneurship. Dissemination via local media further amplified the social impact and supported the potential replication of the program in similar institutions. In conclusion, integrating appropriate technology such as Budikdamber into boarding school settings improves students’ capacity, fosters nutrition awareness, and contributes to achieving the Sustainable Development Goals (SDGs) numbers 2, 3, and 12.